Neslyšící studenti: vysokoškolské studium ve vybraných státech Evropy a srovnání se situací v ČR - Vinklátová, Veronika (Univerzita Karlova, Filozofická fakulta, 2020)
(in English): The topic of the bachelor thesis is a tertiary education of deaf students. Its aim is to map the conditions of university studies for deaf students in selected European countries (Bulgaria, Ireland, Iceland, Poland, Russia and Sweden) and to compare it with the current situation in the Czech Republic. Attention is paid to relevant legal and procedural documents, financial support for universities to create conditions suitable for the studies of deaf students, specific "support measures" and the organization of their provision. This is an overview thesis, focusing on nationwide (standardized) procedures, not a thesis providing case studies describing the situation of specific students in specific schools. Information about the situation in selected European countries was obtained mainly through an electronic questionnaire survey among "national respondents" active in the university environment in the field of so-called Deaf Studies. (česky) Tématem bakalářské práce je terciální vzdělávání neslyšících studentů. Jejím cílem je zmapování podmínek univerzitního studia neslyšících studentů ve vybraných státech Evropy (Bulharska, Irska, Islandu, Polska, Ruska a Švédska) a srovnání se současnou situací v České republice. Pozornost je věnována relevantním dokumentům legislativní a procesní povahy, finanční podpoře vysokých škol k vytváření podmínek vhodných pro studium neslyšících studentů, konkrétním "podpůrným opatřením" a organizaci jejich poskytování. Jedná se o práci přehledovou, zaměřující se na celostátní (standardizované) postupy, nikoli o práci přinášející případové studie popisující situaci konkrétních studentů na konkrétních školách. Informace o situaci ve vybraných státech Evropy byly získány zejm. prostřednictvím elektronického dotazníkového šetření mezi "národními respondenty" činnými v univerzitním prostředí v oblasti tzv. Deaf Studies. Institut of Deaf Studies Ústav jazyků a komunikace neslyšících Filozofická fakulta Faculty of Arts